Time performance of scoop stretcher versus vacuum mattress for prehospital spinal stabilization: open-label simulation-based randomized controlled trial - Loric Stuby; David Thurre (Emergency Care Journal, 2024)
Recent research has yielded conflicting results on the use of spinal stabilization in prehospital care, with some guidelines expressing concerns about its potential lack of benefit or harm. Transportation on a backboard can cause pain, discomfort, and pressure ulcers, whereas the log-roll technique can cause unnecessary movement and aggravate existing injuries. The scoop stretcher and vacuum mattress provide comparable or better immobilization and comfort than the backboard. Prehospital time is critical, and patients with life-threatening conditions should undergo rapid stabilization procedures. Despite this, some studies have overlooked the scoop stretcher as a spinal stabilization device. The primary goal was to compare the time required to achieve spinal stabilization using a scoop stretcher versus a vacuum mattress. This was a monocentric, parallel, randomized (sealed envelope), superiority, open-label, controlled simulation experiment. All student paramedics, registered paramedics, and EMTs who work in the participating EMS were eligible to participate in the study apart of the study team. The experimental group had to use a scoop stretcher, whereas the control group used a vacuum mattress. Fifteen participants were included. The scoop stretcher group required less time to complete the stabilization procedure (median [Q1; Q3]: 127 seconds [111;145] versus 212 [156;237], p=0.005). Using a scoop stretcher for spinal stabilization is more time-efficient than a vacuum mattress, making it a viable option for unstable trauma patients in the prehospital setting. More research is needed to determine its efficacy in actual clinical practice.